Gerakan Literasi Membaca Sebagai Penumbuh Kreativitas Siswa di SMP Al Islam Kartasura - Sahana, Rossy Tiara; Salasabila, Devina Putri; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2024)
Through the literacy movement, it is hoped that schools can foster student creativity, especially reading and writing skills. For example, at AL Islam Kartasulra Middlel School which implelmelnts thel school litelracy movelmelnt as onel way to delvellop stuldelnt crelativity. Thel aim of this relselarch is to obtain data on how schools delvellop stuldelnt crelativity throulgh thel relading litelracy movelmelnt at AL Islam Kartasulra Middlel School. This relselarch ulsels an obselrvational melthod, namelly direlct obselrvation telchniqulels in thel classroom, looking at intelractions beltweleln stuldelnts and telachelrs and vicel velrsa. Data collection techniques are interview and documentation. Thel typel of relselarch ulseld in this writing is a casel stuldy procelss that analyzels the effort of SMP AL Islam Kartasulra Middle School in fostering crelativity throulgh thel relading litelracy movelmelnt. Thel relsullts of thel relselarch show: 1) Relading Cornelr in elvelry cornelr in thel classroom, 2)Litelracy elxtraculrricullar throulgh thel relading litelracy movelmelnt with variouls school elfforts, stuldelnts can fostelr thelir crelativity, namelly: 1) making magazinels and sticking thelm on thel school wall 2 ) painting and postelr making skills.